Cardiovascular Events, Malignancies, and Efficacy Outcomes in Latin American Patients With Rheumatoid Arthritis Receiving Tofacitinib or Tumor Necrosis Factor Inhibitors - Gustavo Citera; Eduardo Mysler; Adriana María Kakehasi; Virginia Pascual‐Ramos; Walter Massón; Mary Jane Cadatal; Jose L. Rivas; Farzad Sheibanie; Claudia Helling; Darío Ponce de León (2024)
Background/Objective To assess safety/efficacy of tofacitinib and tumor necrosis factor inhibitors (TNFi) in patients from Latin America (LATAM) in ORAL Surveillance. Methods In ORAL Surveillance, 4362 patients with rheumatoid arthritis aged ≥50 years with ≥1 additional cardiovascular risk factor received tofacitinib 5 or 10 mg twice daily or TNFi. This post hoc analysis stratified patients by geographical location (LATAM, n = 1202; non-LATAM, n = 3160). Incidence rates (IRs; patients with first event/100 patient-years) and hazard ratios for adverse events of special interest were reported. Efficacy outcomes included Clinical Disease Activity Index and American College of Rheumatology 20/50/70 responses. Results Risk factors associated with cardiovascular disease and malignancies were less prevalent in the LATAM cohort compared with the non-LATAM cohort. IRs for patients receiving tofacitinib (combined doses) versus TNFi were 0.54 versus 0.28 (LATAM) and 1.14 versus 0.92 (non-LATAM) for major adverse cardiovascular events; 0.58 versus 0.27 (LATAM) and 1.33 versus 0.95 (non-LATAM) for malignancies excluding nonmelanoma skin cancer; and 0.69 versus 0.35 (LATAM) and 0.63 versus 0.33 (non-LATAM) for all-cause death. IRs for nonmelanoma skin cancer and venous thromboembolism were also numerically higher with tofacitinib versus TNFi and in the non-LATAM cohort versus LATAM. Efficacy was similar across treatment groups within each cohort. Conclusions Adverse events of special interest were generally less frequent in LATAM versus non-LATAM patients, reflecting differences in baseline characteristics, and higher with tofacitinib versus TNFi in both cohorts, consistent with the overall findings of ORAL Surveillance. Our findings emphasize the importance of assessing individual risk factors to guide benefit/risk assessment and treatment decisions. Clinical trial registration number NCT02092467